An overview of the post-graduate physiology education in Turkey - YEGEN, BERRAK (DEOMED PUBL, ISTANBUL, 2017)
A questionnaire was prepared to determine the current situation, characteristics, main problems and solution proposals of post-graduate physiology education in Turkey. The questionnaire was answered by 40% of the physiology departments with post-graduate programs. The results of the questionnaire demonstrate that 31% of master students and 45% of PhD students have academic positions. Most of the post-graduate physiology students are employed in the academic staff training program (62% of master and 59% of PhD students). Post-graduate physiology students were mainly composed of biologists (25%) and medical doctors (21%). All or the majority (81%) of postgraduate students have completed their education within the legal periods. We have observed that post-graduate physiology students do not sufficiently benefit from the national and international student exchange programs, scholarships and do not participate in academic activities. Publication rates of the post-graduate thesis in national and international journals are also below the anticipated level. The general problems faced in providing post-graduate physiology education are insufficiency of available academic positions, scholarships, number of academic staff, inadequate financial support in producing qualified research as well as lack of infrastructure. The results of the questionnaire demonstrate that comprehensive studies with broad participation are necessary in order to improve post-graduate education in our country.
Keywords: Physiology; post-graduate education; problems; solution proposals